Challenges for Protection of Future HVDC Grids - Pérez-Molina, María José; Larruskain, D. Marene; Eguía López, Pablo; Buigues, Garikoitz (Frontiers in Energy Research, 2020)
Nowadays, high voltage direct current (HVDC) transmissions are gaining relevance in long distance and renewable energy integration projects over the conventional alternating current (AC) transmissions due to several advantages as improved flexibility and independent active and reactive power controllability. Despite that, the high currents and voltage collapses generated by fault conditions in HVDC systems imply some unresolved technical challenges regarding the detection, location and clearance of faults. Faults have to be cleared in a very short time range in order to minimize their impact on the system. For this objective, very fast protection algorithms and reliable HVDC circuit breakers are required. This paper focuses on the technical challenges and limitations of HVDC protection systems. This way, protection requirements and different types of measurement devices are considered. Protection algorithms are classified into local-measurement-based and communication-based, highlighting the most important characteristics. In addition, the different technologies of HVDC circuit breakers are compared. Finally, the characteristics and effects of the different available fault-clearing strategies are presented.